2018
DOI: 10.1073/pnas.1811818115
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated histone modifications and chromatin reorganization in a single cell revealed by FRET biosensors

Abstract: The dramatic reorganization of chromatin during mitosis is perhaps one of the most fundamental of all cell processes. It remains unclear how epigenetic histone modifications, despite their crucial roles in regulating chromatin architectures, are dynamically coordinated with chromatin reorganization in controlling this process. We have developed and characterized biosensors with high sensitivity and specificity based on fluorescence resonance energy transfer (FRET). These biosensors were incorporated into nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 58 publications
(71 reference statements)
5
38
0
Order By: Relevance
“…Third, we employed a FRET-based heterochromatin sensor to investigate the effects of HP1α and uSTAT3 on global heterochromatin levels. The heterochromatin FRET sensor consists of peptides of H3 and HP1 fused to YFP and CFP, respectively, which has been previously used as a robust readout of H3K9me3 levels when expressed by transfection [48][49][50]. We found that, as expected, altering HP1α levels, by overexpressing HP1α or expressing a small hairpin (sh) HP1α RNA, affect global heterochromatin levels, as indicated by the FRET sensor ( Fig.…”
Section: Ustat3 Promotes Heterochromatin Formationsupporting
confidence: 55%
“…Third, we employed a FRET-based heterochromatin sensor to investigate the effects of HP1α and uSTAT3 on global heterochromatin levels. The heterochromatin FRET sensor consists of peptides of H3 and HP1 fused to YFP and CFP, respectively, which has been previously used as a robust readout of H3K9me3 levels when expressed by transfection [48][49][50]. We found that, as expected, altering HP1α levels, by overexpressing HP1α or expressing a small hairpin (sh) HP1α RNA, affect global heterochromatin levels, as indicated by the FRET sensor ( Fig.…”
Section: Ustat3 Promotes Heterochromatin Formationsupporting
confidence: 55%
“…In the past two decades, genetically-encoded FRET biosensors have served as a critical tool in revealing spatially and temporally dynamic signalling networks regulated by GPCRs in cultured cells. Many FRET-based sensors have now been created, allowing the optical detection of a wide range of signalling processes including second messengers, ion flux, protein kinases, monomeric GTPases, post-translational modifications and protein-protein interactions 1215,53 . In contrast, the in vivo application of intracellular signalling-related FRET biosensors is much less developed, especially in freely-moving animals.…”
Section: Discussionmentioning
confidence: 99%
“…Among these technologies, fiber photometry has emerged as the least invasive, most accessible and affordable approach for recording neural activity in freely moving rodents 710 . Many intracellular signalling biosensors have been developed which utilize changes in Förster resonance energy transfer (FRET) between two fluorescent proteins 11 , in order to report levels or activity of second messengers, protein kinases, GTPases, post-translational modifications and protein-protein interactions 1215 . These tools have been widely used to dissect signaling pathways in cultured cells and have recently begun to be applied in vivo , aided by recent technological developments such as intravital imaging 14,16 , microendoscopy 3 , 2-photon microscopy 2,5,6,17 and fluorescence lifetime measurement 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The intensity images were pre-processed and deconvoluted in external software packages such as MetaMorph and MetaFluo (Figure S7). The 3D snapshot is colored by the FRET/ECFP ratio values of a new histone-localized histone 3 lysine 9 tri-methylation (H3K9me3) FRET biosensor at the intensity isosurface of the histone 3 [21]. The color represents level of epigenetic H3K9 tri-methylation at the surface of condensed histone in a dividing HeLa cell.…”
Section: Movie and 3d Visualizationmentioning
confidence: 99%
“…The source code, documentation and example data are freely available at our group website and GitHub. The ratiometric image analysis functionalities of Fluocell have been extensively tested by us and other groups [15][16][17][18][19][20][21]. In addition, Fluocell also contains a previously published Diffusion module for image-based FRAP analysis, as well as intensity-based polarity analysis functions which have been used to quantify the spatial distribution of PI3K and Rac1 in polarized cells seeded on micropatterns [22][23][24].…”
Section: Introductionmentioning
confidence: 99%